Ultrasonography as a diagnostic tool in acute appendicitis: Rural setup - Lamani, Yamanur P.; Goudar, Bhimanagouda V.; Kalburgi, Eshwar B.; Bhavi, Bheemappa K.; Karikazi, Mohmmedgouse (International Surgery Journal, 2017)
Background: Despite technological advances the diagnosis of appendicitis is still based primarily clinical assessment. The diagnosis of atypical appendicitis remains clinically challenging and is one of the most commonly missed problems in the emergency department. Ultrasonography is highly operator dependent with a consequently wide reported sensitivity range. Methods: This is a prospective study conducted in the department of surgery. All patients with right lower abdominal pain, admitted to HSK hospital Bagalkot, in whom acute appendicitis was suspected were analysed from January 2013 to June 2014. Results: In the present study appendix was visualized in 85% of the patients and periappendiceal collection was found in 7% of patients. Faecolith was found only in 1 case. Out of these 74 cases were uncomplicated acute appendicitis. Perforated acute appendicitis was diagnosed in 6 cases. One case was diagnosed as appendicular abscess and 4 cases were diagnosed as chronic appendicitis. Based on clinical assessment 4 patients were subjected to surgery after 48hours. Conclusions: Graded compression US remains our first line method in rural setup in the evaluation of patients referred with clinically suspected acute appendicitis.